Water Supply and Sanitation Policies, Institutions, and Regulation : Adapting to a Changing World - Synthesis Report - World Bank (Washington, DC, 2022)
Policies, institutions, and regulation (PIR) are essential to achieving the Sustainable Development Goals (SDGs) related to water and sanitation, but need a considerable boost to be effective. A rich body of analytical work has been developed to support this idea. Nevertheless, this report argues that the mainstreaming and implementation of PIR into concrete reforms, investment programs and infrastructure is still sporadic at best. At the same time, the stakes for getting PIR right are higher than ever. PIR needs to be strengthened, adjusted, and scaled up to meet the needs of a changing world. The World Bank has reviewed the experience of various countries with PIR and has documented its insights in a new report. This report has two main objectives. The first is to reflect on the body of PIR knowledge and experiences accumulated globally and in selected countries to refine the PIR concept based on lessons learned. The second is to advocate for greater action on PIR by policy makers, development partners, international financial institutions, and civil society by using projects and investments as implementation vehicles. A companion piece to this report, the PIR Framework Tool, provides more detailed guidance on undertaking policy dialogue on PIR, identifying reform options, and applying PIR concretely in practice.